Export Oriented Agriculture in the Agri-History of India - Prasad, Rajendra; Shivay, Yashbir Singh (International Journal of Bio-resource and Stress Management, 2020)
India’s agricultural research has the main emphasis on food grains production and rightly so because of short food supply and dependence on import of wheat from USA. Now the country has become self-sufficient in food and its research needs re-orientation because, most farmers remain below poverty line. Some attention was paid to traditional commercial crops such as cotton, sugarcane and potato for raising the level of farmers above poverty lines, but when they had surplus in production of these crops, they could not export these, because it was difficult to compete in the international market. Nevertheless, there are some herbal crops, where it can compete fairly well in the international export. For example, it has global monopoly in isabgol / psyllium and is topmost exporter in turmeric and only next to China in ginger. However, to maintain these positions in herbal crops in the international export market, India needs to invest a little more in agricultural, scientific and marketing research. Agricultural research is needed to develop high yielding varieties and their agronomy with higher content of main active chemicals and of course market research for new countries to export. Government of India needs to identify more such crops, the areas where they are grown and provide necessary research, processing facilities and procurement at pre-fixed price to facilitate their production and export. This will bring home the much needed foreign exchange and certainly raise the status of some farmers above the poverty line.